Hussain Jawid and Kazakh poetry of early 20th century: spiritual quest and artistic features - Sharip А.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
At the beginning of the twentieth century a number of leading writers, actively participating in the spiritual life of the Turkic peoples, left rich literary heritage in subsequent generations. One of them is Hussain Jawid, the Azerbaijan poet and playwright, the “East Shakespeare”. Unfortunately, his works are unfamiliar to the Kazakh reader. The main reason for this is the systematic mismatch of interpreting practices and the lack of scientific research on the Kazakh-Azerbaijan literary relations. That’s why literary critics have a lot of new goals and objectives. The phenomena in the literature of the two peoples, mainly known only by classics such as Nizami Ganzhaui, Abai Kunanbayev, Myrza-Fatali Akhundzade, should be firstly compared to the comparative-historical method. In this article, romanticism in the poems of Hussain Jawid, in conjunction with contemporary Kazakh poets (M. Zhumabayev, M. Dulatov, S.Toraigyrov, B.Kuleev), is ideologically-artistic in that period of the development of the literature of both countries, from the canal is proved by concrete examples